Praktyki postne w wybranych relacjach pisarzy kościelnych greckich i łacińskich I-III wieku - Kasprzak, Dariusz Antoni (Vox Patrum, 2020)
The practice of religious fasting in the first three centuries of Christianity seems to have been culturally conditioned. Christian individual fasting on Wednesdays and Fridays was most likely a borrowing from the practice of the Essenes of Qumran (see Didache), as opposed to the individual fasting practiced observed by Pharisees. At that time Christians fasted in a similar way as Jews did, i.e., before the Christian Passover – from the sunrise of the previous day (Thursday) to the sunset of the next day (Friday). The Jewish and Christian post-1st-century traditions seem to coincide in increasing the number of fasting days, which was motivated in both religious traditions by apocalyptic revelations. As for the divergence in the fasting traditions, the Pharisaic Jews would fast on Mondays and Thursdays without food and drink from sunrise to sunset of those days. On the other hand, Christians would fast on Wednesdays and Fridays merely living on bread and water, from sunrise to three o’clock. In the texts written by Alexandrian Christians of the turn of the third century, we find a synthesis of the Christian tradition of fasting and the ascetic and dietary philosophies of the Stoic and Platonic philosophy. Alexandrian writers laid more emphasis on temperance as a virtue and a diet as a choice rather than on religious fasting as such. On the other hand, in the Montanistic practices of two-week xerophagy we find the origin of a longer, fortnights’ fast before the Christian Passover. Until the third century, the Catholic Church called the two fasting days directly preceding Easter “Great Fast”. Up to the third century, official fasting was prescribed relatively seldom in the Church (before baptism and for two days before Passover). Individual fasting was practiced on Wednesdays and Fridays. It seems that longer fasting times were recognized in the Church up to the third century as a manifestation of false revelations or heresies.